2017
DOI: 10.1515/raon-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion kurtosis imaging of gliomas grades II and III - a study of perilesional tumor infiltration, tumor grades and subtypes at clinical presentation

Abstract: BackgroundDiffusion kurtosis imaging (DKI) allows for assessment of diffusion influenced by microcellular structures. We analyzed DKI in suspected low-grade gliomas prior to histopathological diagnosis. The aim was to investigate if diffusion parameters in the perilesional normal-appearing white matter (NAWM) differed from contralesional white matter, and to investigate differences between glioma malignancy grades II and III and glioma subtypes (astrocytomas and oligodendrogliomas).Patients and methodsForty-ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 43 publications
4
37
1
1
Order By: Relevance
“…In addition to the solid region, the pWM also showed decreased kurtosis metrics than the surrounding white matter regions. This is consistent with the study of Delgado et al that showed significant differences in DKI metrics from the pWM as compared to cNAWM in a mixed group of 35 patients with grade II and III lesions . The result shows that tumorigenesis effects in LGGs are seen in surrounding WM regions, which has been demonstrated using histologic studies …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In addition to the solid region, the pWM also showed decreased kurtosis metrics than the surrounding white matter regions. This is consistent with the study of Delgado et al that showed significant differences in DKI metrics from the pWM as compared to cNAWM in a mixed group of 35 patients with grade II and III lesions . The result shows that tumorigenesis effects in LGGs are seen in surrounding WM regions, which has been demonstrated using histologic studies …”
Section: Discussionsupporting
confidence: 92%
“…This study showed mean, radial, and axial kurtosis metrics to be more sensitive to diffuse changes in the pWM with larger effect sizes than corresponding diffusion metrics in delineating the pWM from lesion tissue, whereas AK provided the largest increase in effect size in discriminating pWM from cNAWM. This is contrary to the finding reported by Delgado et al that showed no significant differences in AK between pWM and cNAWM . The discrepancy may be due to the heterogeneity in gliomas induced by the amalgamation of grade II and III gliomas in their study, which included 23 grades II and 12 grade III gliomas.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations